Acidophilic and acidotolerant fungi in mud and salt crusts collected from Wadi El- Natrun lakes - Hassan A. Gouda (Journal of Agriculture, Food and Environment)
Isolation some fungi from extreme source under extreme media and these were 42 species related to 14 generaof acidiphilic or/ aciditolerant fungi were collect-ed from mud and salt crusts of Wadi El-Natrun lakes on Czapek Dox agar ad-justed at pH 4 and pH 5 during the seasons of study.Aspergillus andPenicilli-um were the most common generaof the total propogules on the two pH levels.